To the origins of the Cathari myth: The “Good Christians” throughout European history and literature (5th–21st centuries) (Colloquia Comparativa Litterarum, 2025)
Alain Vuillemin. To the Origins of the Cathari Myth: The “Good Christians” throughout European History and Literature (5th–21st centuries). Cordes-sur-Ciel, France, Rafael de Surtis Publishers, 2024, 379 p.